Investigating the nutritional status, outcomes and needs of adolescents and young adults (AYA) following a cancer diagnosis: protocol for a mixed-methods study - Andrew Murnane; Erin Laing; Belinda Steer; Jeremy Lewin; Heather Gilbertson; Elizabeth Mount; Mary-Anne Silvers; Jenelle Loeliger; Jodie Bartle; Kristin Mellett; June Savva; Pasquale L. Fedele; et al. (BMC Cancer)
Abstract Background Cancer treatment for adolescents and young adults (AYA) can be highly challenging and interferes with optimal nutrition, which is vital for healthy development, physical growth, and well-being. Cancer malnutrition and associated negative outcomes are well-studied in adult and paediatric populations, but the specific nutrition complications and requirements for AYA with cancer are poorly understood. This study aims to explore and describe the nutritional status, needs and outcomes of AYA after a diagnosis of cancer. Methods and analysis The AYCANN-study (adolescent and young adult cancer nutrition project) adopts a mixed-methods study design, conducted over three inter-related studies; (1) Prospective observational study of AYA between 15 and 25 years, following diagnosis of any cancer type, to quantitatively assess changes in body weight, muscle mass/function, nutritional status, and health related quality of life (HRQoL). Study assessments will be undertaken at four time-points (recruitment, and 2- 4- and 6-months post-recruitment) and will include screening for nutrition risk (PNST or MST); assessment of nutritional status (PG-SGA, mid-upper arm circumference); assessment of muscle strength (hand-grip strength); frequency of dietitian referral, nutrition support and symptoms; and assessment of health-related quality of life (AQoL-6D); (2) Qualitative study using focus groups with AYA to assess access to nutrition related care and preference for nutrition services; (3) Qualitative study, utilising focus groups with oncology healthcare professionals (OHP) to explore and assess current access to nutrition-related care for AYA following a cancer diagnosis along with OHP nutrition education needs, service delivery and research priority areas. For study 1, statistical analysis will be primarily descriptive, and effect size estimates (Cohen’s d) will be used to characterise any differences between nutritional status groups at follow-up assessments. Thematic analysis will be undertaken for study 2 and 3 to understand patients and OHP access to and experience of nutrition-related care. Discussion This multi-site longitudinal study will explore and describe the nutritional status, needs and nutrition-related outcomes of AYA after a cancer diagnosis. Results will inform future clinical practice guidelines and interventional nutrition research targeting patients identified at greater risk of nutritional complications.